Healthy diets for sustainable food systems: a narrative review - Arrieta, Ezequiel Martín (2023)
To face the challenge of feeding a growing population that changes its lifestyles and diets while trying to conserve natural resources and to protect biodiversity, there are three main strategies to achieve such sustainability goals: (1) changing current agricultural practices, (2) reducing losses and waste throughout the food production and processing chain, and (3) promoting healthy and sustainable diets. Strategies (1) and (2) are important and they are part of the academic, government and industrial agenda, but strategy (3) has been given little attention so far. However, increasing the efficiency of the production, processing and distribution of foods (strategies 1 and 2) may trigger unexpected rebound effects that could offset the gains. Hence, addressing the demand-side by promoting (and facilitating) healthy and sustainable food choices is a valuable tool to contribute to the sustainability of food systems. In this narrative review we (1) explored the environmental impacts of the global food system; (2) reviewed the role of efficiency improvement in agricultural activities to mitigate the environmental impact of food production; (3) summarized the limitations related to technical and technological changes due to the rebound effect; and (4) reviewed what healthy eating is and why it is the central piece of a sustainable food system.